The Ministry of Desire: Anxiety and entrepreneurship in a bureaucracy - Hallur Tor Sigurdarson (Copenhagen Business School (CBS), 2016)
Since the early 1980s there has been a call for entrepreneurship and innovation in the public sector. The call became an international discourse with considerable implications for public administration. Accordingly, bureaucracy is a ubiquitous hindrance for entrepreneurial practices and many of the solutions proposed for public sector bureaucracy draw on research and practices in the private sector and are guided by economic rationality. Instead of adopting this common critique and its set of solutions, in this dissertation a different approach is developed to enquire into the capacity of a bureaucratically organised Ministerial Department to entrepreneur. The approach involves an emphasis on local practices, affects and movements in an ethnographically inspired study. The result is also an idea – local and contextual – of the relationship between entrepreneurship and bureaucracy, which is distant from the entrepreneurship/bureaucracy dichotomy.
hdl:10398/9377
Keywords: 650